Beetroot's crude aqueous extract photosensitizer-Formic acid-Sodium Lauryl Sulphate photogalvanic electrolyte: Solar power and storage. (June 2022) - Koli, Pooran; Pareek, Ramesh Kumar; Dayma, Yashodhara; Kumar, Rajendra
Abstract: Crude aqueous extract of Beetroot has been used as a natural photo-sensitizer for photogalvanic solar power and storage. Beet's root extract-based photogalvanic cell shows improved electrical performance (power 674.4 μW, efficiency 15.31%) and follow the same principles as followed by synthetic photo-sensitizers based photogalvanics. Betalains have been characterized as the main light-absorbing molecules present in the extract. The concentrations and photo-thermal stability of Betalains have been studied for their future perspective. The estimated ground state and excited state potential values (vs NHE) of Betalain are as 0.9015 V and 1.3565 V, respectively, and it matches the published data. On the basis of standard reduction potential and electrochemical series, it is established that the reductant donates an electron to the excited state of pigment, and ground-state Betalain pigment donates an electron to the reductant. The same pattern of electron transfer is also reported for earlier photogalvanics. Graphical abstract: Unlabelled Image Highlights: Beetroot's extract has been studied for photogalvanic solar power and storage. Betalains in extract have been characterized as main light harvesting molecules. Estimated ground and excited state potentials of Betalains is 0.90 V and 1.35 V. Beet's root extract based PG cells shows improved electrical performance. The observed power and current is 674.4 μW, and 3200 μA, respectively.